Analysis of Facilities and Community Friendliness on Tourist Satisfaction in Osing Village, Banyuwangi - Nizhar Al Naufal Syahrizha; Estikowati; Aprilia Rachmadian; Ani Puspawigati; Sari Yuniarti (Jurnal Penelitian, 2025)
Osing Village is one of the tourist destinations in Banyuwangi Regency with its main attraction being the local wisdom of the people in the village. This study aims to determine and analyze the impact of facilities and community friendliness on tourist satisfaction at the Osing Village tourist destination in Banyuwangi Regency. The research method used is explanatory research with 105 respondents of Osing Village visitors as samples, this study uses multiple linear regression data analysis and hypothesis testing. The results of this study show that the facilities and friendliness of the Osing Village community have an effect on tourist satisfaction, and facilities have a dominant effect on tourist satisfaction, which means that the facilities provided by the Osing Village manager are good and can provide satisfaction for tourists who visit, not only facilities but the friendliness of the community in Osing Village also provides a level of tourist satisfaction. The conclusion of this study is that the facilities and friendliness of the community have an effect on the level of tourist satisfaction in Osing Village, Banyuwangi Regency.